Nicaragua Agriculture Public Expenditure Review - World Bank (Washington, DC, 2015)
Agriculture remains fundamental for Nicaragua from both a macroeconomic and social view. It is the largest sector of the Nicaraguan economy, and it remains the single biggest employer with around 30 percent of the labor force and including processed foods, like meat and sugar, agriculture accounts for around 40 percent of total exports value. Nicaragua appears to be gradually losing competitive edge of some of its key agricultural exports within the most important export markets. Agricultural total factor productivity of certain basic goods has been falling, which could be attributed to some extent for the limited use of improved technologies and the gaps in terms of the quality of its infrastructure and logistics services even though there have been some progress in this regard. In spite of these trends, Nicaragua has the potential to expand production sustainably, on both the extensive and the intensive margins.